New perspectives on microbiome and nutrient sequestration in soil aggregates during long‐term grazing exclusion - Ju, Wenliang; Fang, Linchuan; Shen, Guoting; Delgado‐Baquerizo, Manuel; Chen, Ji; Zhou, Guiyao; Ma, Dengke; Bing, Haijian; Liu, Lei; Liu, Ji; Jin, Xiaolian; Guo, Liang; et al. (Global change biology, 2024)
Grazing exclusion alters grassland soil aggregation, microbiome composition, and biogeochemical processes. However, the long‐term effects of grazing exclusion on the microbial communities and nutrient dynamics within soil aggregates remain unclear. We conducted a 36‐year exclusion experiment to investigate how grazing exclusion affects the soil microbial community and the associated soil functions within soil aggregates in a semiarid grassland. Long‐term (36 years) grazing exclusion induced a shift in microbial communities, especially in the <2 mm aggregates, from high to low diversity compared to the grazing control. The reduced microbial diversity was accompanied by instability of fungal communities, extended distribution of fungal pathogens to >2 mm aggregates, and reduced carbon (C) sequestration potential thus revealing a negative impact of long‐term GE. In contrast, 11–26 years of grazing exclusion greatly increased C sequestration and promoted nutrient cycling in soil aggregates and associated microbial functional genes. Moreover, the environmental characteristics of microhabitats (e.g., soil pH) altered the soil microbiome and strongly contributed to C sequestration. Our findings reveal new evidence from soil microbiology for optimizing grazing exclusion duration to maintain multiple belowground ecosystem functions, providing promising suggestions for climate‐smart and resource‐efficient grasslands. We linked the soil microscale‐associated microbiomes with the carbon sequestration and biogeochemical cycling of livestock excluded grasslands for up to 36 years. Long‐term grazing exclusion reduced microbial diversity, community stability, and microbial functional genes associated with carbon sequestration and nutrient cycling. Moreover, we emphasize that the interaction between grazing exclusion and longevity as well as the structure of soil aggregates have substantial impacts the grassland biogeochemical cycles and global climate change in which the soil microbiome is involved.